Tree carbon stock analysis in education forest KHDTK Wanadipa UNDIP, Semarang - Saputro, Rizky Wahyu; Izzati, Munifatul; Yusuf, Muh (BIORE Scientia Publisher, 2024)
Global warming occurs due to increased gases from human activity. Efforts that can be made to minimize global warming are through the forestry sector. Trees play an ecological role, namely as carbon sinks and biomass storage throughout the plant body. The purpose of this study was to analyze the estimated value of carbon stocks in tree biomass in the Special Purposes Forest Area (SPFA) Wanadipa UNDIP Semarang Regency. The sampling method used for measuring tree biomass is the non-destructive method. The non-destructive method is a method that is carried out without destroying or taking all parts of the plant. Data analysis used was the calculation of tree biomass and carbon stocks, and statistical tests of the effect of tree diameter and tree height on carbon stocks in tree biomass. The research station that has the highest carbon stock value is the conservation block of 213,621.25 kg/ha or 213.62 tons/ha. The species that have the highest carbon stock value are Tectona grandis (Jati) and Swietenia mahagoni (Mahoni) in the research block. The amount of carbon that is increasing in the atmosphere at this time must be balanced with the amount of absorption, one of which is by conserving forests, namely through regular tree planting and paying attention to their regeneration, so that trees in carrying out their ecological role can be maintained.